Keanekaragaman Jenis Burung di Kawasan Jaboi Kecamatan Sukajaya Kota Sabang Aceh - Muzkiati Muzkiati; Samsul Kamal; Rizky Ahadi; Elita Agustina; Nafisah Hanim (Program Studi Pendidikan Biologi, 2025)
This study aims to identify bird species and analyze the diversity, species richness, evenness, and dominance of birds in the Jaboi area, Sukajaya District, Sabang City. The method used was direct survey through visual observation and recording of birds found across various habitat types during the study period. The results revealed 21 bird species from 13 families with a total of 128 individuals. The house sparrow (Passer domesticus) was the most abundant species with 30 individuals, while some species such as the white-bellied sea eagle (Haliaeetus leucoryphus), spotted dove (Spilopelia chinensis), and emerald dove (Chalcophaps indica) were each represented by only one individual. The family Columbidae dominated the bird population with 19%. The Shannon diversity index (Ĥ) was 2.405, indicating moderate diversity, while the species richness index was 3.916, reflecting a moderate level of richness. The evenness index (E) was 0.803, suggesting a fairly even distribution of individuals across species, categorized as moderate to high. Additionally, the dominance index was 0.401, indicating that no single species dominated the bird community in the area. In conclusion, the Jaboi area in Sukajaya District, Sabang City, exhibits moderate bird diversity and richness with a relatively even distribution of individuals, and no species dominance, reflecting a balanced and stable community structure.